KEBIJAKAN PENANGANAN GELANDANGAN PENGEMIS BERBASIS PANTI UNTUK KEBERFUNGSIAN SOSIAL PEMERLU PELAYANAN KESEJAHTERAAN SOSIAL (PPKS) (STUDI PADA PANTI PELAYANAN SOSIAL PENGEMIS GELANDANGAN ORANG TERLANTAR MARDI UTOMO SEMARANG) - Maryatun Maryatun; Santoso Tri Raharjo; Budi Muhammad Taftazani (Kebijakan : Jurnal Ilmu Administrasi, 2022)
Central Java is a province with a large number of homeless people and beggars, namely 1,582 people, with a low ratio of availability of nursing homes for homeless people (1:8). Based on data from the Central Statistics Agency (BPS) in 2020, Central Java Province experienced an increase in poverty rates and population density from 3.74 million to 3.98 million people, so the number of homeless beggars increased. The purpose of this study was to determine the implementation of policies for handling homeless beggars at the Mardi Utomo Homeless People's Homeless Social Service Home (PPSPGOT) Semarang at each stage in order to know the indicators, supporting factors, and obstacles in the field so that efforts can be made to improve the handling optimally. This is a descriptive, qualitative study with secondary data sources derived from literature studies, documentation, books, articles, and journals from related research and primary data from interviews with the orphanage. The results showed that the handling of homeless beggars was carried out through the initial approach stage, the understanding and understanding stage of the problem, the problem-solving development stage, the problem-solving stage, the resocialization stage, and the termination stage. There are supporting and inhibiting factors in dealing with the homeless and beggars, so efforts are needed to improve in order to achieve the goals of independence and welfare. Keywords: handling homeless beggars, orphanage-based, social functioning.